2019
DOI: 10.3390/s19235248
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Marker miRNAs, Associated with Prostate Cancer, in Plasma Using SOI-NW Biosensor in Direct and Inversion Modes

Abstract: Information about the characteristics of measuring chips according to their storage conditions is of great importance for clinical diagnosis. In our present work, we have studied the capability of chips to detect nanowire biosensors when they are either freshly prepared or have been stored for either one or two years in a clean room. Potential to detect DNA oligonucleotides (oDNAs)—synthetic analogues of microRNAs (miRNAs) 198 and 429 that are associated with the development of prostate cancer (PCa)—in buffer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…In our previous papers, we also demonstrated that the (nanowire biosensor)-based approach can be successfully employed for the detection of protein [ 32 , 43 , 44 , 49 ] and nucleic acid [ 41 , 42 , 50 ] biomolecules in plasma samples. Herein, the SOI-NW sensor chips with high-quality sensor chips has been demonstrated to be suitable for the highly sensitive detection (3.3 × 10 −17 M) of relatively small nucleic acid molecules in both purified buffer solutions and plasma samples.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous papers, we also demonstrated that the (nanowire biosensor)-based approach can be successfully employed for the detection of protein [ 32 , 43 , 44 , 49 ] and nucleic acid [ 41 , 42 , 50 ] biomolecules in plasma samples. Herein, the SOI-NW sensor chips with high-quality sensor chips has been demonstrated to be suitable for the highly sensitive detection (3.3 × 10 −17 M) of relatively small nucleic acid molecules in both purified buffer solutions and plasma samples.…”
Section: Discussionmentioning
confidence: 99%
“…The use of biosensors with sensor elements of nanometer size-such as nanowires and nanoribbons-opens new horizons in biomedical research. These biosensors allow one to perform direct label-free detection of various targets-such as viral particles [6] and biological macromolecules (proteins [7][8][9][10][11][12][13] and nucleic acids [14][15][16][17][18][19])-in real time, attaining low (<1 fM, i.e., <10 −15 M) concentration detection limits [20]. The principle of operation of these biosensors consists of recording a modulation of an electric current, flowing through the sensor elements, in the course of binding of target particles (i.e., macromolecules or viral particles of interest) to their surface.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, thin film sensors and nanosensors are widely adopted for this mission because of their advantages in sensitivity [ 5 , 6 , 7 ]. Among these sensors, SiNWs-FET sensors have received increasing attention as they have ultrahigh sensitivity, which is necessary for the detection of these samples [ 8 , 9 , 10 , 11 ]. There are many factors, such as debye length [ 12 ], surface binding sites [ 13 ] and molecular affinities [ 14 ], that affect the sensitivity of SiNWs-FET sensors.…”
Section: Introductionmentioning
confidence: 99%